AB0716 ESTABLISHMENT OF BASDAI CUT-OFFS FOR THE DISEASE ACTIVITY STATES BASED ON ASDAS CUT-OFFS IN TAIWANESE ANKYLOSING SPONDYLITIS PATIENTS. (June 2019) - Chen, Hsin-Hua; Pan, Ting-I; Chen, Yi-Ming; Chen, Yi-Hsing; Huang, Wen-Nan; Hsieh, Tsu-Yi; Lai, Kuo-Lung; Hung, Wei-Ting; Chou, Yin-Yi; Tseng, Chih-Wei; Wu, Yi-Da; Hsieh, Chia-Wei; et al.
Abstract : Background: The Bath ankylosing Spondylitis Disease activity index (BASDAI) has been widely utilized to evaluate disease activity in patients with ankylosing spondylitis (AS). However, the cut-off of BASDAI used to indicate high disease activity (i.e., ≥4) was determined arbitrarily and was suggested as a criterion to initiate biological therapy for aS patients. The ankylosing Spondylitis Disease activity Score (ASDAS) has been developed as a new composite index to assess aS disease activity. The cut-off values for disease activity states has been defined and validated. ASDAS≥2.1 was selected as a criterion of starting biological therapy. However, the BASDAI cut-off values corresponding to the aSDAS cut-off values for disease activity states were unknown. Objectives: The purpose of this study was to estimate the corresponding BASDAI and aSDAS cut-off in a Taiwanese aS cohort. Methods: Since November 2016, we assessed the ankylosing Spondylitis Disease activity Score (ASDAS) and the Bath ankylosing Spondylitis Disease activity index (BASDAI) regularly and recorded demographic data, comorbidity, family history, medication use for aS patients in Taichung Veterans General hospital (TCVGH) using an electronic patient reported data system linked to an electronic medical record system. We identified 489 aS patients with complete baseline demographic and assessment data from the TCVGH electronic data system during 2016/11–2018/10. We used receiver operating characteristic (ROC) curves with Youden's J statistic to determine the cut-off values of BASDAI that correspond to aSDAS disease activity cut-offs (i.e., 1.3, 2.1 and 3.5). Results: We included a total of 489 aS patients [114 (23.3%) females, mean age 44.1 years (S.D. 13.9), mean symptom duration 18.0 years (S.D. 11.9), 152 (31.1%) current biologic users]. Mean BASDAI, aSDAS-ESR and aSDAS-CRP scores were 2.1 (S.D. 1.5), 1.6 (S.D. 0.8) and 1.5 (S.D. 0.9) respectively. Mean levels of CRP and ESR were 0.6 (S.D. 1.5) mg/dl and 12.2 (S.D. 14.0) mm/hr respectively. Based on aSDAS-CRP, the numbers (%) of aS patients with inactive disease (<1.3), low disease activity (1.3-2.1), high disease activity (2.1-3.5) and very high disease activity (≥3.5) were 210 (42.9), 171 (35.0), 88 (18.0) and 20 (4.1) respectively. Based on aSDAS-ESR, the numbers (%) of aS patients with inactive disease, low disease activity, high disease activity and very high disease activity were 202 (41.3), 174 (35.6), 96 (19.6) and 17 (3.5) respectively. The best trade-off BASDAI values corresponding to aSDAS -CRP 1.3, 2.1 and 3.5 were 2.1, 3.1 and 3.7 respectively. The optimal BASDAI values corresponding to aSDAS-ESR 1.3, 2.1 and 3.5 were 2.0, 2.6 and 4.8 respectively. Conclusion: The estimated optimal BASDAI value that corresponds to the recommended aSDAS cut-off ≥2.1 for biologial therapy initiation was lower than the recommended BASDAI cut-off of ≥4 in this Taiwanese aS cohort. References: [1] Machado P, et al. 2011. Ankylosing Spondylitis Disease activity Score (ASDAS): defining cut-off values for disease activity states and improvement scores. Ann Rheum Dis2011;70:47-53. Disclosure of interests: Hsin-Hua Chen Speakers bureau: Johnson & Johnson, Novartis, Pfizer, abbvie, Roche, UCB, Bristol-Myers Squibb, Chugai, Ting-I Pan: None declared, Yi-Ming Chen Grant/research support from: GSK, Pfizer, BMS, astra & Zeneca, Consultant for: Pfizer, Novartis, abbvie, Johnson & Johnson, BMS, Roche, Sanofi, MSD, Guigai, astellas, inova Diagnostics, UCB, agnitio Science Technology, United Biopharma, thermo Fisher, Paid instructor for: Pfizer, Novartis, abbvie, Johnson & Johnson, BMS, Roche, astra& Zeneca, Sanofi, MSD, Guigai, astellas, UCB, thermo Fisher, Speakers bureau: Pfizer, Novartis, abbvie, Johnson & Johnson, BMS, Roche, Lilly, GSK, astra& Zeneca, Sanofi, MSD, Guigai, astellas, UCB, thermo Fisher, Yi-Hsing Chen: None declared, Wen-Nan Huang: None declared, Tsu-Yi Hsieh: None declared, Kuo-Lung Lai: None declared, Wei-Ting Hung: None declared, Yin-Yi Chou: None declared, Chih-Wei Tseng: None declared, Yi-Da Wu: None declared, Chia-Wei Hsieh: None declared, Ching-Tsai Lin: None declared